Cosmeceutical Peptides in the Framework of Sustainable Wellness Economy - Errante, Fosca; Ledwoń, Patrycja; Latajka, Rafal; Rovero, Paolo; Papini, Anna Maria (Frontiers in Chemistry, 2020)
Among the many aspects that contribute to the wellness of each individual, healthy and younger-looking skin play a relevant role, as clearly shown by the important growth of the skin-care products market observed in recent years. In this scenario, the field of cosmeceuticals appears particularly promising, being based on cosmetic products containing active ingredients. Among these, several peptides were proposed for cosmeceutical applications, thanks to their specific interaction with biological targets. In this mini-review, we report some of the most investigated and used peptides for cosmetic formulations, taking into account that cosmeceutical peptides are basically divided into three main categories, i.e., neurotransmitter inhibitors, carriers, and signal peptides. Special attention was payed to the scientific studies supporting the claimed biological activity of these peptides, as a fundamental aspect that should underpin the growth of this field in the framework of a sustainable wellness economy.